Effects of protein and amino-acid supplementation on athletic performance - Kreider, R. B. (Sportscience, 1999)
This review evaluates the theoretical rationale and potential effects on athletic performance of protein, purported anabolic amino acids, branched-chain amino acids, glutamine, creatine, and hydroxymethylbutyrate (HMB). FINDINGS: Dietary supplementation of protein beyond that necessary to maintain nitrogen balance does not provide additional benefits for thletes. Ingesting carbohydrate with protein prior to or following exercise may reduce catabolism, promote glycogen resynthesis, or promote a more anabolic hormonal environment. Whether employing these strategies during training enhances performance is not yet clear. There is some evidence from clinical studies that certain amino acids (e.g., arginine, histidine, lysine, methionine, ornithine, and phenylalanine) have anabolic effects by stimulating the release of growth hormone, insulin, and/or glucocorticoids, but there is little evidence that supplementation of these amino acids enhances athletic performance. Branched-chain amino acids (leucine, isoleucine, and valine) and glutamine may be involved in exercise-induced central fatigue and immune suppression, but their ergogenic value as supplements is equivocal at present. Most studies indicate that creatine supplementation may be an effective and safe way to enhance performance of intermittent high-intensity exercise and to enhance adaptations to training. Supplementation with hydroxymethylbutyrate appears to reduce catabolism and increase gains in strength and fat-free mass in untrained individuals initiating training; as yet, limited data are available to decide how it affects training adaptations in athletes. CONCLUSIONS: Of the nutrients reviewed, creatine appears to have the greatest ergogenic potential for athletes involved in intense training.